A study of the relationship of family functioning, self-regulation and antisocial behaviour among adolescents - Chin, Sie Zhen; Lee, Chie Hwa; Ng, Samantha Kuet Ch'ng (2019)
There is a rise in juvenile crimes from the years 2009 to 2016 in which the family and adolescents’ self-regulation play crucial roles in the formation of adolescent antisocial behaviour. The current study aimed to investigate the relationship between family functioning in six aspects (problem-solving, roles, behaviour control, affective involvement, affective responsiveness, and communication) and adolescents’ self-regulation on adolescent antisocial behaviour. 225 respondents were recruited from two identified secondary hotspot schools in Selangor through purposive sampling. Data was collected through self-administered questionnaires. The current study found that all six subfactors in family functioning and selfregulation were significantly associated with adolescents’ antisocial behaviour; while selfregulation significantly predicted antisocial behaviour. Improving the quality of family functioning and promoting a holistically healthy adolescent development can mitigate adolescents’ antisocial behaviour.